(untitled) (Homoeopathy for All, 2025)
Cardiovascular diseases fall under major cause of morbidity and mortality and is considered a rapidly growing problem worldwide. It is estimated that over 40 million Indians have some kind of cardio vascular diseases. The symptom manifest most often as chest pain or chest discomfort. The best way to reduce the incidences of cardiac diseases is by avoiding or minimizing the risk factors that triggers the disease. The efforts to control life style diseases which are major risk factors for cardio vascular diseases will definitely contribute to the cardio vascular disease prevention. Homeopathy offers a significant complementary role in the management of cardiovascular diseases, can be either preventive, curative or palliative. Materia medica has number of medicines that could be effective in managing the cases of MI. It is proved helpful in eliminating the risk factors, preventing the progress of disease, and preventing sudden death and morbidity due to myocardial ischemia.